Validation of the optimal scaffold pore size of nasal implants using the 3-dimensional culture technique - Jeoung Hyun Nam; So Yun Lee; Galina Khan; Eun Soo Park (Archives of Plastic Surgery, 2020)
Background To produce patient-specific nasal implants, it is necessary to harvest and grow autologous cartilage. It is crucial to the proliferation and growth of these cells for scaffolds similar to the extracellular matrix to be prepared. The pore size of the scaffold is critical to cell growth and interaction. Thus, the goal of this study was to determine the optimal pore size for the growth of chondrocytes and fibroblasts. Methods Porous disc-shaped scaffolds with 100-, 200-, 300-, and 400-µm pores were produced using polycaprolactone (PCL). Chondrocytes and fibroblasts were cultured after seeding the scaffolds with these cells, and morphologic evaluation was performed on days 2, 14, 28, and 56 after cell seeding. On each of those days, the number of viable cells was evaluated quantitatively using an MTT assay. Results The number of cells had moderately increased by day 28. This increase was noteworthy for the 300- and 400-µm pore sizes for fibroblasts; otherwise, no remarkable difference was observed at any size except the 100-µm pore size for chondrocytes. By day 56, the number of cells was observed to increase with pore size, and the number of chondrocytes had markedly increased at the 400-µm pore size. The findings of the morphologic evaluation were consistent with those of the quantitative evaluation. Conclusions Experiments using disc-type PCL scaffolds showed (via both morphologic and quantitative analysis) that chondrocytes and fibroblasts proliferated most extensively at the 400-µm pore size in 56 days of culture.